Kinerja Humas Universitas Islam Negeri (UIN) Raden Fatah Palembang Dalam Persepsi Wartawan Palembang Ekspres (Palpres) - Ricky Candra; Amin Sihabuddin; Jufrizal (CV. ITTC INDONESIA, 2024)
Every organization or company, whatever its type, definitely needs a public relations function for the sustainability of the organization. As public relations in one of the educational institutions, public relations of UIN Raden Fatah Palembang functions as a two-way communication tool to foster harmonious relationships both for the general public and for the internal public (university scope). By collaborating with the mass media, this will certainly produce a positive impact. So here the author aims to find out the role of public relations performance at Raden Fatah State Islamic University (UIN) Palembang. And to find out how the public relations performance of UIN Raden Fatah Palembang is perceived by Palembang Ekspress (Palpres) journalists. The research method used by the author in this research is a qualitative descriptive method by conducting direct observations in the field and seeking information through observation and interviews. And resulted in a discussion regarding the public relations performance of UIN Raden Fatah Palembang, and how Palembang Express journalists perceive the public relations performance of UIN Raden Fatah Palembang. The conclusion drawn from this research is that the public relations performance of Raden Fatah State Islamic University (UIN) Palembang, public relations has carried out its duties and functions as a publication media, both news and information regarding activities inside and outside the university via websites and social media. Not only that, now UIN Raden Fatah Palembang's public relations also utilizes mass media as a medium for disseminating information, and this produces good output and input for UIN Raden Fatah Palembang's public relations. Then, the public relations officer at the State Islamic University (UIN) Raden Fatah Palembang, in the perception of Palembang Ekspres journalists, the public relations officer at UIN Raden Fatah Palembang has successfully carried out public relations activities and is considered to be very good at carrying out its roles and functions. Even though there were several obstacles in the collaboration that occurred, this did not hamper the communication and collaboration process that occurred.